Discrete human dihydrofolate reductase gene transcripts present in polysomal RNA map with their 5' ends several hundred nucleotides upstream of the main mRNA start site. - Masters, J N (1985)
The 5' ends of dihydrofolate reductase (DHFR)-specific transcripts have been mapped in the 5'-flanking region of the amplified DHFR gene of the human methotrexate-resistant cell line 6A3 by primer extension and S1 protection experiments. The main 5' end, at position -71 relative to the first nucleotide of the DHFR reading frame, corresponds to the recently identified main transcription initiation site for the DHFR gene and pertains to transcripts representing approximately 99% of the DHFR-specific polysomal polyadenylic acid-containing RNA, and including the previously described DHFR mRNAs with sizes of 3.8, 1.0, and 0.8 kilobases. At least six other minor 5' ends have been mapped to nucleotide positions -449 to -480 upstream of the DHFR gene and pertain to approximately 1% of the DHFR-specific polysomal polyadenylic acid-containing RNA. These upstream initiating transcripts appear to include five major discrete species with sizes of 4.3, 3.8, 3.1, 2.1, and 1.0 kilobases and four minor ones with sizes of 7.3, 5.0, 1.4, and 0.8 kilobases. These species, with the exception of those of 3.1- and 2.1-kilobase sizes, also have been found in VA2-B cells, the parental line of 6A3, and in HeLa cells. The upstream initiating transcripts present in all three cell lines are increased in amount in 6A3 cells as compared with the other cell lines, in about the same proportion as the three identified DHFR mRNAs.